The Life and Scientific Work Of Zahid Kawthari - Khabibidinov Boburshakh Abduvali ugli (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
The article provides information about the life and scientific work of the scholar Zahid Kathari, who worked and lived  in Turkey and Egypt in the late 19th and early 20th centuries. In addition, it touches on various difficulties encountered in his life path and the various debates in scientific circles. The refutations against subversive ideas were also provided.